Relationship between Body Mass Index and Cardiovascular Fitness Levels of Junior High School Students - Ari Ardianto; Baiq Satrianingsih; Intan Primayanti; Johan Wahyudi (Universitas Riau, 2025)
This study aims to examine the relationship between Body Mass Index (BMI) and cardiovascular fitness levels among students at SMP IT Darul Wahdah Gerung in 2025. A quantitative approach with a correlational research design was employed. Data were collected by measuring students’ body weight and height to calculate BMI, as well as administering the 12-minute Cooper test to assess cardiovascular fitness levels. Pearson’s correlation test was used for data analysis. The results revealed that; (1) there was a significant relationship between Body Mass Index (BMI) and students’ cardiovascular fitness levels, as indicated by a correlation coefficient of −0.689 and a significance value of 0.005 (p < 0.05). Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. (2) The negative correlation coefficient indicates a significant inverse relationship, meaning that higher BMI values are associated with lower cardiovascular fitness levels, and vice versa.